A relação entre sistemas de gestão da qualidade e desempenho organizacional : um estudo de empresas do setor metalmecânico da serra gaúcha - Sfreddo, Leonardo Stertz (My University, 2018)
There is no definitive conclusion, in the international literature, about the impact of quality management system in the organizational performance. Besides that, few studies analyzed if the quality management system and processes maturity affect the performance. Considering these gaps, this study analyzes the relation between quality management system and organizational performance (operational, market and economic-financial) in metal mechanic companies of the Serra Gaúcha region. The study was divided into two phases, the first following a qualitative approach, by deep interviews with the company mangers of the studied sector, and the second following a quantitative approach, developed by a survey with the managers of companies in the studied sector. The results show that: i) the companies in the sample have maturity levels in quality and processes management above the average point of the scale (3); ii) statistically there are no significant differences of maturity and performance between ISO 9001certified and non-certified companies; iii) the quality management system maturity positively impacts market and economic-financial performance, however it does not impact in the companies’ operational performance; and iv) the maturity of processes management only impacts in the companies’ operational performance. These results allow concluding that there is space for increasing maturity in quality management and processes management in the metal mechanic companies of the studied region. Therefore it is suggested the implementation of actions in this sense, once those tend to improve the companies’ performance, regardless of whether or not they search for ISO 9001 certification
Na literatura internacional não se observa uma conclusão definitiva quanto ao impacto dos sistemas de gestão da qualidade no desempenho organizacional. Além disso, poucos estudos analisam se o nível de maturidade dos sistemas de gestão da qualidade e dos processos afetam o desempenho. Dadas essas lacunas, o presente trabalho visou analisar a relação entre sistemas de gestão da qualidade e desempenho organizacional (operacional, de mercado e econômicofinanceiro) em empresas do setor metalmecânico da Serra Gaúcha. O trabalho foi desenvolvido em duas etapas, a primeira com abordagem qualitativa, operacionalizada mediante entrevistas em profundidade com gestores de empresas do setor estudado, e a segunda com abordagem quantitativa, desenvolvida por meio de uma survey com as empresas desse setor. Os resultados evidenciaram que: i) as empresas da amostra possuem níveis de maturidade em gestão da qualidade e gestão de processos superiores ao ponto central da escala utilizada; ii) não há diferenças estatisticamente significantes de maturidade e desempenho entre empresas certificadas e não certificadas pela Norma ISO 9001; iii) a maturidade do sistema de gestão da qualidade impacta positivamente nos desempenhos de mercado e econômico-financeiro, porém não impacta no desempenho operacional das organizações; e iv) a maturidade da gestão de processos impacta somente no desempenho operacional das empresas. Esses resultados permitem concluir que há espaço para aumento da maturidade em gestão de qualidade e gestão de processos nas empresas metalmecânicas da região estudada. Portanto, sugere-se a implementação de ações nesse sentido, uma vez que as mesmas tendem a melhorar o desempenho das empresas, independentemente da busca ou não da certificação ISO 9001.
Keywords: Controle de qualidade; Desenvolvimento organizacional; Metalúrgicas - Indústria - Serra, Região (RS); Quality control; Organizational change; Metalurgics - Industry - Serra, Region (RS)